Production and characterization of biomass pellet effect towards the energy application - Teng, Swee Xim (2016)
Biomass describes as the type of renewable energy source plays an important role in the future energy balance. Biomass appears to be a promising alternative energy source to replace fossil fuels in the future as it is abundantly available. However, it presents several undesired properties that do not permit its direct exploitation. One of the biomass called oil palm trunk (OPT) which is in bulky condition and contains high moisture contents. Hence this study is to improve the properties of OPT residues toward an efficient renewable energy supply by using pelletization and torrefaction process. Pelletization is a compression process to increase the energy content. In this study, one specific ratio with 90wt% OPT fibers or powder and 10% starch as binding agent will be tested in the experiment to produce a quality OPT pellet. Torrefaction is an emerging thermochemical pre-treatment process that improves the fuel properties of OPT pellet. In this study, three temperatures: 200˚C, 250˚C, and 300˚C at a constant heating rate of 10˚C/min for 30minutes, 60minutes and 90minutes residence time are to investigate the properties of OPT pellet. The torrefied product is characterized in term of mass and energy yield of OPT pellet. The trend of the mass yield graph for torrefied fiber was decreased from 81.88% to63.51% while torrefied powder was decreased from 89.60% to 74.09% when temperature increased along the torrefaction process. This was due to the degradation of lignocellulosic components of samples during the experiment. While for the trend of the energy yield of the samples were increased as torrefaction temperature and residence time increased. The highest energy yield was 89.7% at 300°C and 30minutes while the lowest energy yield was 40.7% at 200°C at 90 minutes. From the analysis, FTIR analyzed the lignocellulosic components while SEM analyzed morphology of torrefied OPT pellet.